Study on the Influence of Poly-V Belt Effective Length Extreme Deviation on Diesel EFEADS Performance - Decheng Wang; Pengchao Sui; Dongling Ma; Chao Zeng; Shi Cheng (Jixie chuandong)
The transverse vibration equation is obtained by establishing the balance equation of poly-V belt and tensioner and coupling vibration model of pulley and poly-V belt. The influence of different extreme deviations on the dynamic performance of EFEADS is analyzed by calibrating and modifying the simulation model. Result shows that the maximum swing of tensioning arm reduced under the increasing of extreme deviation. At medium and high speed，the larger extreme deviation caused EFEADS instability and the swing of tensioning arm increasing. In addition，it caused the entire increasing of transverse vibration. But，the changing tension force lead to variation of resonance frequency and caused corresponding rotary speed by transverse vibration peak drifted at different speed. The smaller the extreme deviation caused the greater the belt tension and the lesser transverse vibration.